THE TRAINING SYSTEM OF A FOOTBALL COACH-LECTURER (HISTORICAL ASPECT) - SVIERTNIEV, O.; SHERSTYUK, O. (Педагогічні науки, 2022)
The article focuses on historical background of the origin and development of a football coach-lecturer training system. It was logically ascertained that the system reveals to have durable timeline up from the end of the XIX c. until nowadays. All the crucial stages of the successful implementation of football into the educational system of Ukraine were deeply clarified. Actually, the profound interest in football as powerful means of physical education has been exposed in Western Ukraine since 1890. He was Oleksii Butovskyi, a head of training courses for physical education specialists in Cadet corps, who explored British football content and game instructions firstly in the domestic practice of physical education. The football training programme for pupils of 5–8 grades was initiated by Uzhhorod gymnasium gymnastics teacher I. Medretskyi, while E. Tsenar and H. Yordan as professors at Lviv teacher’s gymnasium presented the first programme of the football implementation in gymnasiums. The fact that training courses, produced and adopted in 1896 by Petr Lesgaft (Lesgaft Courses), became higher educational institution to master leaders and organizers in physical education was under in-depth analysis. It was also pointed out that foundation of the physical education faculties (PEF) within pedagogical institutions of higher education manifested a significant stage to solve the problem of training scientific-pedagogical staff. They actually started a regular training of physical education teachers as well as coaches-lecturers for educational institutions. The role of public organizations in training football coaches-lecturers under the up-to-date terms was thoroughly examined.